2012
DOI: 10.1200/jco.2011.39.7901
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Treatment Response As an Early Response Indicator for Patients With Rectal Cancer

Abstract: Treatment response to neoadjuvant chemoradiotherapy among patients with locally advanced rectal cancer undergoing radical resection is an early surrogate marker and correlate to oncologic outcomes. These data provide guidance with response-stratified oncologic benchmarks for comparisons of novel treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
348
1
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 446 publications
(398 citation statements)
references
References 21 publications
24
348
1
14
Order By: Relevance
“…With a reduced incidence of BRAF mutations one would expect dMMR rectal cancer to have an improved prognosis, however, initial prognostic studies were conflicting. One reported 5-year overall survival (OS) of 50% for 22 dMMR rectal cancers (Samowitz et al, 2009), and another reported 3-year disease free survival (DFS) of 90% for 20 dMMR rectal cancers (Hong et al, 2012), Nevertheless, in the largest, most recent clinical series dMMR rectal cancer was confirmed to have an outstanding prognosis compared with pMMR disease, with a 5-year OS and DFS of 90.6% (de Rosa et al, 2016) and 70% (Park et al, 2012) respectively for locally advanced rectal cancer and 5-year OS of 50% for metastatic CRC (Brouquet et al, 2010).…”
Section: Rectal Cancer With Msimentioning
confidence: 99%
See 1 more Smart Citation
“…With a reduced incidence of BRAF mutations one would expect dMMR rectal cancer to have an improved prognosis, however, initial prognostic studies were conflicting. One reported 5-year overall survival (OS) of 50% for 22 dMMR rectal cancers (Samowitz et al, 2009), and another reported 3-year disease free survival (DFS) of 90% for 20 dMMR rectal cancers (Hong et al, 2012), Nevertheless, in the largest, most recent clinical series dMMR rectal cancer was confirmed to have an outstanding prognosis compared with pMMR disease, with a 5-year OS and DFS of 90.6% (de Rosa et al, 2016) and 70% (Park et al, 2012) respectively for locally advanced rectal cancer and 5-year OS of 50% for metastatic CRC (Brouquet et al, 2010).…”
Section: Rectal Cancer With Msimentioning
confidence: 99%
“…Early small series with little clinical detail and much heterogeneity reported rates of pathologic response between 0 and 60% (Bertolini et al, 2007;Cecchin et al, 2011;Charara et al, 2004;Lim et al, 2015;Shin et al, 2013). However, in the largest series to date pathologic response was found to be excellent, with a complete pathologic response (pCR) of 27.6% in locally advanced disease (de Rosa et al, 2016) compared to a pCR rate of 18% among patients without LS treated with neoadjuvant chemoradiation (Park et al, 2012). Importantly, dMMR rectal cancer's hypermutator phenotype, characterised by antigen formation and an enhanced immune response, may contribute to its favorable outcomes, highlighting the potential for emerging immunotherapeutic strategies .…”
Section: Rectal Cancer With Msimentioning
confidence: 99%
“…An increasing number of studies performed with functional imaging techniques, including contrastenhanced dynamic MRI/computed tomography and 18F-fluorodeoxyglucose (18FDG) positron emission tomography in patients treated with standard CRT, shows the capability to obtain an early prediction of response by comparing basal versus intermediate evaluations of response to therapy [74][75][76][77][78][79][80][81].…”
Section: Predictive Factorsmentioning
confidence: 99%
“…Radiotherapy doses of 45 to 50 Gy with concomitant chemotherapy yield a clinical complete response (CCR) rate between 10.4% [3] and 27% [4]. e pathological complete response (PCR) can be higher, up to 35.1% [4][5][6][7]. Brachytherapy or orthovoltage boost approaches can yield a CCR of about 81% in selected patients [8,9].…”
Section: Introductionmentioning
confidence: 99%